Ecological processes shaping Central Patagonian salt marsh landscapes - Idaszkin, Yanina Lorena (2011)
Plant zonation is one of the most conspicuous ecological features of salt marshes worldwide. In this work we used a combination of field transplant and greenhouse experiments to evaluate the importance of interspecific interactions and physical stress in the determination of the major plant zonation patterns in Central Patagonian salt marshes. There, Spartina alterniflora dominates the low marsh, and Sarcocornia perennis the high marsh. We addressed two questions: (i) What prevents Spartina alterniflora from colonizing the Sarcocornia perennis-dominated high marsh zone? and (ii) What prevents Sarcocornia perennis from colonizing the Spartina alterniflora-dominated low marsh zone? Our experimental transplants combined with neighbour exclusion treatments showed that the presence of Sarcocornia perennis negatively affects Spartina alterniflora, preventing it from surviving and/or spreading. Complementary field transplant and greenhouse experiments showed that Sarcocornia perennis did not survive the frequent tidal submersion by approximately 1.5m of turbid seawater in the Spartina alterniflora zone, but its survival was independent of the presence of Spartina neighbours, and of the strong soil anoxia as well. Our results suggest that Spartina alterniflora is excluded by Sarcocornia perennis towards the low marsh, where frequent and prolonged submersion limit the survival of the latter. We provide and discuss key baseline information to facilitate the future design of ecophysiological experiments designed to accurately identify the exact mechanisms acting in every situation.